The increasing of mechanical characteristics of high-test cast iron - V. A. Chaikin; V. V. Ishutin (Литьë и металлургия)
There is summerized the experience of slugs production for the running system of automobile engines from high- test cast iron of mark VCh-40. There is shown, that graphitizing processing of melt by blend modifier on the basis of active carbon and silicon alows to elevate considerably the plastic characteristics of VCh, produced by modification in mould.